2021
DOI: 10.1093/ije/dyab168.355
|View full text |Cite
|
Sign up to set email alerts
|

1139Predictors of Unintended Pregnancy among Indian women: An analysis from NFHS-IV Survey

Abstract: Background Low levels of women’s decision-making over control of sexual intercourse, contraceptive use, domestic violence with intimate partners not only have impact on socioeconomic and cultural aspects but also on unintended pregnancies. Which create serious public health issues associated with physical, reproductive and mental health consequences. This study explores associations between domestic violence, maternity and sociodemographic characteristics with unintended pregnancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A substantial amount of research on unintended pregnancy among women has revealed that socioeconomic factors like younger age (15-19 years), poor economic background, being illiterate, and rural place of residence are important predictors of unintended pregnancies (8,9). Women who do not use contraception and face domestic violence also in uenced unintended pregnancy among women (10).…”
mentioning
confidence: 99%
“…A substantial amount of research on unintended pregnancy among women has revealed that socioeconomic factors like younger age (15-19 years), poor economic background, being illiterate, and rural place of residence are important predictors of unintended pregnancies (8,9). Women who do not use contraception and face domestic violence also in uenced unintended pregnancy among women (10).…”
mentioning
confidence: 99%